1991
DOI: 10.1159/000182114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase Inhibitor, Pravastatin, on Corticosteroid Metabolism in Patients with Heterozygous Familial Hypercholesterolemia

Abstract: The present study examined whether hypolipidemic therapy with a potent 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, pravastatin, influences corticosteroid metabolism in patients with heterozygous familial hypercholesterolemia (FH). Urinary excretion of tetrahydrocortisone, tetrahydrocortisol, 6β-hydroxycortisol and free cortisol were determined in 22 patients with heterozygous FH before and after pravastatin administration (10 mg/day for 2 months). Pravastatin induced a statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Assessment of gonadal hormone production in women receiving lipid‐lowering therapy is complicated by the menstrual cycle and menopause and has thus not been studied extensively. In men, most statin studies have not found any impairment in testosterone production . Similarly, we did not find any change in serum testosterone or gonadotropins during this study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Assessment of gonadal hormone production in women receiving lipid‐lowering therapy is complicated by the menstrual cycle and menopause and has thus not been studied extensively. In men, most statin studies have not found any impairment in testosterone production . Similarly, we did not find any change in serum testosterone or gonadotropins during this study.…”
Section: Discussionsupporting
confidence: 64%
“…For statins, multiple studies have shown that the adrenal gland continues to synthesize cortisol normally, despite marked LDL lowering . However, even in patients with markedly impaired LDL receptor function (ie, homozygous familial hypercholesterolaemia), adrenal function is normal and remains normal on lipid‐lowering therapy .…”
Section: Discussionmentioning
confidence: 99%
“…35,36 The impact of statins on adrenal function has been studied in multiple populations with a wide variety of statins. 23,[25][26][27][28][29]31,32,[37][38][39][40][41][42][43][44][45] None of these studies showed clinically relevant impairment of adrenal function, secondary to statin therapy. Patients with heterozygous or homozygous familial hypercholesterolemia could also theoretically be at increased risk of adrenal dysfunction because of their reduced capacity to use LDL receptor-mediated cholesterol uptake.…”
Section: 22mentioning
confidence: 97%